Implementasi Gudang Garam: Edukasi Bahaya Nikotin dan Begadang Pada Remaja Desa Sungai Asam - Maria Ulfah; Annisa Febriana; Anisa Maidawati; Angeline Duana Yashintia Nugroho; Muhammad Riza; Mutmainnah Mutmainnah; Dessy Damayanti; Risma Dwi Rahmawati; Nur Safitri (Jurnal Medika: Medika, 2026)
Adolescents are an age group vulnerable to risky behaviors such as smoking and staying up late, which can negatively affect both physical and psychological health. Limited knowledge about the dangers of nicotine and sleep pattern disturbances is one of the factors contributing to the high prevalence of these behaviors. This community service activity aimed to implement the GUDANG GARAM program (Gerakan Ubah Diri, Akhiri Nikotin dan Begadang, Gapai Raga Aman dan Menyehatkan) through health education to improve adolescents’ knowledge in Sungai Asam Village. The program applied an educational approach through health counseling using posters and leaflets, accompanied by pretest and posttest evaluations to measure changes in participants’ knowledge. A total of 26 adolescents participated in all stages of the program. The evaluation results showed an increase in the average knowledge score from 6.73 before the intervention to 8.42 after the educational session, indicating improved understanding regarding the dangers of nicotine and staying up late. In addition, the activity was conducted interactively through discussions and question-and-answer sessions, which enhanced adolescent participation in the learning process. The implementation of the GUDANG GARAM program was proven to improve adolescent health literacy and has the potential to serve as a promotive and preventive strategy in fostering healthy lifestyle behaviors within the community. This program is recommended to be implemented sustainably with support from families and the community to optimize behavioral change outcomes.